Non-Financial Compensation, Job Satisfaction, and Employee Performance at PT. Rum East Great Ternate - Lawarang, Rutsfi U.; Rajak, Adnan; Kamis, Ruslan A.; Arilaha, Muhammad Asril (AIBPM Publisher, 2023)
This study aims to determine and analyze the effect of non-financial compensation and job satisfaction on employee performance at PT. Rum East Great Ternate. The total sample of the study was 35 employees. The test tool used is multiple linear regression analysis. The results showed that non-financial compensation and job satisfaction had a positive and significant effect both partially and simultaneously on employee performance. Keywords: Non-Financial Compensation, Job Satisfaction, and Employee Performance